(NfAWORIT(B: [(NrOMAN(B]; s (NeGO IMPERATRICA(B: [(NkNIGA (B1] / s (N~ASTX (B3s - (NpIKULX(B, (NwALENTINs ((NmOSKWA(B: s (NgOLOS(B, s, 1991)
(NrOMAN (B"(NfAWORIT(B" (NWOSSOZDAET [IROKOE ISTORI^ESKOE HUDOVESTWENNOE POLOTNO rOSSII WTOROJ POLOWINY (BXVIII (NWEKA(B.s
rus
Keywords: (NiSTORI^ESKIJ ROMANs